Educação profissional: um estudo do impacto da lei e implantação da reforma do ensino técnico e suas decorrências no CEFET-RS : (1997-2004) - Loponte, Luciana Neves (2006)
This dissertation investigates the implementation of and the resistance movements against the Professional Education Reform Program put into practice through the Executive Law 2.208 dated 1997. This study was based on the experience of the Centro Federal de Educação Tecnológica de Pelotas - CEFET-RS, a Federal Vocational Education Center, from 1997 to 2004, year in which the Executive Law 5.154 was published, along with an analysis of documents from official, school and teachers and civil servants union sources as well as from the results of a research questionnaire given to present teachers of the Center´s technical courses. The research was carried out at two existing units of the CEFET-RS while this investigation was being conducted. In order to verify how the reform implementation process took place, one technical course from each unit was chosen, over which a documental analysis was made. To analyze what the teachers think about the reform, a research questionnaire was applied to a sample of teachers of several technical courses at the CEFET-RS. The field study presents the teachers` opinions concerning both Executive Laws. For the analysis, the following concepts were used: reform, paradigm, autonomy, competences and skills, polytechnic school and unitary school